Crisis of Savignyism Savigny's method to resolving conflict of laws between retention and cancellation) ) (مجلة أبحاث قانونية, 2024)
Conflict  between  laws are resolved by the rules of attribution established by  Germany jurist Savigny, according to which: Analysis  of the relationship,its  focus is in a specific society, and then  the laws of that society are applied to that relationship, In light of globalization, some jurists saw the need to exclude thisclassical methodin favor of other methods  that are more capable of keeping pace with the development of international trade in its modern world. This represents a deliberate denial of Ssvigniesm.
Keywords: Savigny' s method; Conflict of law; Judicial focus; Objective focus